2023
DOI: 10.1002/smll.202300634
|View full text |Cite
|
Sign up to set email alerts
|

Toward High Efficient Cu2ZnSn(Sx,Se1−x)4 Solar Cells: Break the Limitations of VOC and FF

Abstract: Increasing the fill factor (FF) and the open‐circuit voltage (VOC) simultaneously together with non‐decreased short‐circuit current density (JSC) are a challenge for highly efficient Cu2ZnSn(S,Se)4 (CZTSSe) solar cells. Aimed at such target in CZTSSe solar cells, a synergistic strategy to tailor the recombination in the bulk and at the heterojunction interface has been developed, consisting of atomic‐layer deposited aluminum oxide (ALD‐Al2O3) and (NH4)2S treatment. With this strategy, deep‐level CuZn defects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…The main Raman peaks located at 172, 197, and 234 cm −1 were allocated to the kesteritebased CZTSe phase, and the peak in the vicinity of 329 cm −1 should be attributed to kesterite-based CZTS phase, which is in agreement with the published literature. [30,31,35] Apart from those, no other peaks appeared in any of the samples. Raman analysis further confirmed that no peaks of the impurity phases were detected in any of the CZTSSe-based thin films.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…The main Raman peaks located at 172, 197, and 234 cm −1 were allocated to the kesteritebased CZTSe phase, and the peak in the vicinity of 329 cm −1 should be attributed to kesterite-based CZTS phase, which is in agreement with the published literature. [30,31,35] Apart from those, no other peaks appeared in any of the samples. Raman analysis further confirmed that no peaks of the impurity phases were detected in any of the CZTSSe-based thin films.…”
Section: Resultsmentioning
confidence: 83%
“…Additionally, for the three samples, the peak positions of Cu 2p, Zn 2p, and Sn 3d are assigned to +1, +2, and +4 states, respectively. [30,35] As is well-known, the electrical features of the CZTSSe grain boundaries (GBs) play a pivotal role in the transport of carriers, thereby affecting the photovoltaic performance of devices. [54][55][56][57] Kelvin probe force microscopy (KPFM) measurements were conducted to analyse the behaviors of carriers in the CZTSSe-based absorber layer without and with Si substitution, as illustrated in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, successful incorporation of Cd 2+ and Mn 2+ isovalent cations has been achieved in the promising results in CZTSSe TFSCs that mitigate Zn-related defects. However, their performance remains relatively low compared with CIGSSe-based TFSCs. Apart from this, many efforts have been dedicated to achieving low V oc -deficit characteristics in kesterite TFSCs. , Guo et al showed that controlling selenization pressure during the annealing process enables enhanced performance in the CZTSSe TFSCs. Zhang et al also showed that creating a microenvironment with SnSe 2 vapor and preselenization of the surface and back contact can effectively improve the device performance.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from this, many efforts have been dedicated to achieving low V oc -deficit characteristics in kesterite TFSCs. 12,13 Guo et al 14 showed that controlling selenization pressure during the annealing process enables enhanced performance in the CZTSSe TFSCs. Zhang et al 15 also showed that creating a microenvironment with SnSe 2 vapor and preselenization of the surface and back contact can effectively improve the device performance.…”
Section: Introductionmentioning
confidence: 99%